Intracellular location of the histonelike protein HU in Escherichia coli. - Dürrenberger, M (1988)
Immunocytochemical labeling of thin sections of cryosubstituted, Lowicryl-embedded Escherichia coli cells with protein A-colloidal gold was used to study the structural organization of the bacterial nucleoid. We found that the histonelike protein HU was not associated with the bulk DNA in the nucleoid but was located in areas of the cell where metabolically active DNA is associated with ribosomes and where single-stranded DNA, RNA polymerase, and DNA topoisomerase I were also located. The resolution of the methods used did not allow us to decide whether HU was associated either with ribosomes or with transcriptionally active DNA, nor could we demonstrate interaction of HU with either.